Tinjauan Moral Terhadap Perkembangan Biomedik dalam Pelayanan Kesehatan - Mateus Mali (Jurnal Orientasi Baru, 2007)
Since the beginning, medical ethics always walks together with medical practices. For centuries, Hippocratic oath is the guard of the medical practices. But now medical science is growing rapidly so it can be followed by medical ethics. Bioethics is born from this concern. It wants to connect ethics and medical practices and to give ethics orientation for medical services. Bioethics does not talk just about medical practices but about all human life in the front of medical services. This essay will show us the connection between ethics and medical services. Ethics is needed to help us how to use knowledge in medical science. One of the ethics aims is respect for human being. In particular, this essay will speak about: relation between ethics and biomedic, the needs of ethics in the biomedic practices and ethics orientation in medical services.